2019
DOI: 10.1088/1742-5468/ab11da
|View full text |Cite|
|
Sign up to set email alerts
|

Velocity distribution of driven granular gases

Abstract: The granular gas is a paradigm for understanding the effects of inelastic interactions in granular materials. Kinetic theory provides a general theoretical framework for describing the granular gas. Its central result is that the tail of the velocity distribution of a driven granular gas is a stretched exponential that, counterintuitively, decays slower than that of the corresponding elastic gas in equilibrium. However, a derivation of this result starting from a microscopic model is lacking. Here, we obtain a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 72 publications
(140 reference statements)
1
18
0
Order By: Relevance
“…For ballistic transport, the collision rate is proportional to the relative velocity. For mono dispersed gases, an analysis with this more realistic kernel shows that β remains the same, though for r w = 1, there are additional logarithmic corrections to the exponential decay [45,46]. We expect these results to generalise to the driven binary gas also, such that β, as obtained in this paper, is not modified.…”
Section: Summary and Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…For ballistic transport, the collision rate is proportional to the relative velocity. For mono dispersed gases, an analysis with this more realistic kernel shows that β remains the same, though for r w = 1, there are additional logarithmic corrections to the exponential decay [45,46]. We expect these results to generalise to the driven binary gas also, such that β, as obtained in this paper, is not modified.…”
Section: Summary and Discussionsupporting
confidence: 64%
“…Thus, the truncation of the driving term in the Boltzmann equation to lowest order in η gives the correct result only in restricted regimes. However, even this restricted equivalence between microscopic models for driving and Boltzmann equation with diffusive driving may not hold for more realistic collision kernels where the collision rates are proportional to the relative velocity [45,46].…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we choose to study a system with scalar velocities as the analysis there is much simpler (Study of an inelastic gas with two-dimensional velocities may be found in Ref. [72]). For the inelastic gas with scalar velocities, driven homogeneously through dissipative driving, we carry out an exact analysis of the equations satisfied by the moments of the velocity for a general collision kernel, corresponding to arbitrary δ .…”
mentioning
confidence: 99%